The Structure and Use of Mosques in Indonesian Islam: The Case of Medan, North Sumatra - Federspiel, Howard M. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
The mosque has an important position in Islam and Muslim lives. Prophet Muhammad, especially after the migration to Medina, to build a mosque as a center of worship and social activities of Muslims. This paper examines the existence, role and use of mosques in Indonesia, with a case study in Medan, capital of North Sumatra province. Through studies on these aspects, can be seen standing mosque in the contemporary period.DOI:Â 10.15408/sdi.v3i3.800